7- Multiple Discourses On Sexuality Implications For Translating Sexual Wellness Concept Into Action Strategies In A Kenyan Context - Ahlberg, Beth Maina; Kamau, Anne; Maina, Faith; Kulane, Asli (African Sociological Review, 2009)
This Paper attemps to map, drawing mainly from HIV and AIDS prevention interventions, the multiple discourses on sexuality. The aim is to provide a picture of the challenges and opportunities in transforming the concept of sexual wellness currently being articulated. This is a move from the commonly held view of sexuality as a threat to health, to one promoting sexual wellness or positive view of sexuality. A postcolonial conceptual perspective is used to help grasp the multiple-realities emerging from the historical influences on Africa and for reflexivity on the ambivalences and representations of Africa and African culture including sexuality.